2017
DOI: 10.1039/c7ta00258k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical deposition of carbon nanotubes from CO2in CaCl2–NaCl-based melts

Abstract: As part of the efforts to address global climate change, the identification of methods for the capture of carbon dioxide and its selective electrochemical conversion into value-added carbonaceous materials in molten salt electrolytes is a research topic of scientific and technological significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 41 publications
2
51
0
Order By: Relevance
“…In the view of continuous operation, the electrochemical reduction rate should be well matched with that of CO 2 capture, achieving a net transformation of CO 2 . The electrochemical reduction rate can be easily tuned by adjusting the electrode potential and current density [2,22,29] . Therefore, the net CO 2 transformation rate was mainly determined by the CO 2 absorption process.…”
Section: Co 2 Capturementioning
confidence: 99%
See 2 more Smart Citations
“…In the view of continuous operation, the electrochemical reduction rate should be well matched with that of CO 2 capture, achieving a net transformation of CO 2 . The electrochemical reduction rate can be easily tuned by adjusting the electrode potential and current density [2,22,29] . Therefore, the net CO 2 transformation rate was mainly determined by the CO 2 absorption process.…”
Section: Co 2 Capturementioning
confidence: 99%
“…This indicated that the molten salt composition and the absorbents have a significant influence on the CO 2 capture rate. Other conditions such as temperature, agitation and the molten salt depth can also affect the initial CO 2 absorption rate [2,17,22,26,29,32] .…”
Section: Thermodynamics and Kinetics For Co 2 Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of deposition temperature, [23][24][25][29][30][31] substrate, [23,29,30,[32][33][34][35] electrolyte, [29,30,36] current density, [30,37] and potential [4,24,25,32,33,31,35,38] have all been investigated, with a rich and varied library of carbon microstructures being produced, and with links being drawn between the structure of these carbons and the conditions of electrodeposition. In more recent years this understanding of the molten carbonate system has paved the way for an increased understanding of both the mechanism of carbon formation from molten carbonate salts, [39][40][41] and for the application of molten carbonate reduction in attempts to produce carbons with specific properties or morphologies. [31,39,42,43] The research presented here continues from the work of this group, [27,28] which has shown how temperature, current density, substrate, and electrolyte variation influences the morphology of carbonate derived carbons, and how these morphological changes relate to aqueous supercapacitive performance in the materials.…”
mentioning
confidence: 99%
“…In more recent years this understanding of the molten carbonate system has paved the way for an increased understanding of both the mechanism of carbon formation from molten carbonate salts, [39][40][41] and for the application of molten carbonate reduction in attempts to produce carbons with specific properties or morphologies. [31,39,42,43] The research presented here continues from the work of this group, [27,28] which has shown how temperature, current density, substrate, and electrolyte variation influences the morphology of carbonate derived carbons, and how these morphological changes relate to aqueous supercapacitive performance in the materials. [27,28] This has indicated that electrochemical performance in aqueous systems is at its highest for materials showing elevated amorphous character, which contributes to increased double layer formation, [28] and high oxygen functionalization, which leads to high pseudo-capacitance.…”
mentioning
confidence: 99%